L'Afrique dans la diplomatie multilatérale - Smouts, Marie-Claude (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1991)
The difficulties Africa is going through are illustrated in the gap between its growing dependence on international authorities and the continual weakening of the means at its disposal to make it self heard in these bodies. For twenty years, Africa was caught up in the North-South dialogue. In the 1980s, the breaking-off of the dialogue and the breaking-up of the Third World deprived it of means for collective action. The distinction between North Africa and Black Africa has grown more pronounced as first the globalization of markets and then the changes in East-West relations caused the latter to fall victim to a process of double marginalization. International organizations consider Subsaharan Africa to be a "welfare case" and reserve special treatment for it, without loosening the external constraints bearing down on its economy. In these conditions, a consensus seems to be developing which holds that multilateral diplomacy is not what's most important for Africa and that the real question is to know how to involve the entire population in the development process. There is thus a return to the overall issue of grass root organizations and essential needs as outlined in the 1970s.